Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{5}{6}\cdot\frac{7}{12}+\frac{5}{12}\cdot\frac{5}{6}+\frac{1}{6}\)
\(=\frac{5}{6}\cdot\left(\frac{7}{12}+\frac{5}{12}\right)+\frac{1}{6}\)
\(=\frac{5}{6}\cdot1+\frac{1}{6}\)
\(=\frac{5}{6}+\frac{1}{6}\)
\(=1\)
\(\left(\frac{8}{15}\cdot\frac{3}{4}\cdot\frac{5}{4}\right):\frac{7}{8}\)
\(=\frac{4\cdot2\cdot3\cdot5}{3\cdot5\cdot4\cdot2\cdot2}:\frac{7}{8}\)
\(=\frac{1}{2}:\frac{7}{8}\)
\(=\frac{1}{2}\cdot\frac{8}{7}\)
\(=\frac{4}{7}\)
2 + 2 + 2 = 6
3 x 3 - 3 = 6
5 : 5 + 5 = 6
6 + 6 - 6 = 6
7 - 7 : 7 = 6
\(\frac{3}{5}+\frac{6}{4}+\frac{5}{2}=\frac{12}{20}+\frac{30}{20}+\frac{50}{20}+\frac{12+30+50}{20}\\ =\frac{92}{20}=\frac{23}{5}\)
\(\frac{6}{7}+\frac{5}{8}=\frac{48}{56}+\frac{35}{56}=\frac{83}{56}\)
\(\frac{3}{5}-\frac{3}{8}=\frac{24}{40}-\frac{15}{40}=\frac{9}{40}\)
\(\frac{1}{4}+\frac{5}{6}=\frac{6}{24}+\frac{20}{24}=\frac{26}{24}=\frac{13}{12}\)
Chúc bạn học tốt !
(1+1+1)!=6
2+2+2=6
3x3-3=6
√4+√4+√4=6
5+(5:5)=6
6+6-6=6
7-(7:7)=6
√(8:8)+8=6
(9-9)+√9!